Outcome of frail elderly patients with diffuse large B-cell lymphoma prospectively identified by Comprehensive Geriatric Assessment: results from a study of the Fondazione Italiana Linfomi. Issue 1 (January 2014) - Merli, Francesco; Luminari, Stefano; Rossi, Giuseppe; Mammi, Caterina; Marcheselli, Luigi; Ferrari, Angela; Spina, Michele; Tucci, Alessandra; Stelitano, Caterina; Capodanno, Isabella; Fragasso, Alberto; Baldini, Luca; et al.
Abstract In 2003 the Fondazione Italiana Linfomi (FIL) started a clinical research program for investigating initial treatment of frail elderly patients with diffuse large B-cell lymphoma (DLBCL) identified by Comprehensive Geriatric Assessment (CGA). From 2003 to 2006, 334 elderly patients underwent CGA assessment, and 99 patients were classified as frail. Frail patients had a median age of 78 years, stage III–IV disease in 62% and age-adjusted International Prognostic Index (aaIPI) of 2–3 in 53%. Treatment consisted of several different regimens according to physician discretion. After a median follow-up of 36 months, 5-year overall survival (OS) was 28%. In multivariate analysis, aaIPI 2–3 (p = 0.005) and the presence of respiratory comorbidity (p = 0.044) were the only factors that showed independent correlation with OS. Frail patients had a poorer outcome compared with fit patients also if they were treated with rituximab-containing combination chemotherapy (hazard ratio 2.37, 95% confidence interval 1.48–3.78; p < 0.001). CGA is a valid tool to prospectively identify frail subjects among elderly patients with DLBCL.